2006
DOI: 10.1088/0022-3727/39/13/009
|View full text |Cite
|
Sign up to set email alerts
|

Oxide of non-basal quasi-polar 6H-SiC surfaces

Abstract: Non-basal surfaces of 6H-SiC, which are thought to exhibit polar behaviour, were thermally oxidized in steam. The resulting oxide thickness was determined by two methods: a non-contact measurement of the oxide capacitance and a physical measurement of the step height from an etched pattern. The surface was found to oxidize faster than its counterpart, i.e. the surface. When these results were compared with results of the oxidation of the basal {0001} and surfaces, the effective permittivity of the oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…(1102) are then terminated with carbon atoms. An oxidation experiment conducted on 6H-SiC using (1103) and (1103) surfaces, which are somewhat similar to the respective (1102) and (1102) surfaces in 4H-SiC, confirms the model [24]. Despite the lack of data on 4H-SiC, we are confident that silicon termination makes the (1102) and (1102) surfaces behave like etch-stops under anodization conditions, similar to the (0001) face.…”
Section: Model For the Pore Shapesupporting
confidence: 71%
See 1 more Smart Citation
“…(1102) are then terminated with carbon atoms. An oxidation experiment conducted on 6H-SiC using (1103) and (1103) surfaces, which are somewhat similar to the respective (1102) and (1102) surfaces in 4H-SiC, confirms the model [24]. Despite the lack of data on 4H-SiC, we are confident that silicon termination makes the (1102) and (1102) surfaces behave like etch-stops under anodization conditions, similar to the (0001) face.…”
Section: Model For the Pore Shapesupporting
confidence: 71%
“…Nonbasal planes corresponding to pore surfaces are interesting candidates for boule growth experiments, electrical properties studies, and surface science investigations [24][25][26]. Already, low-energy electron diffraction (LEED) and Auger electron spectroscopy (AES) have revealed differences in the composition of the (1102)and (1102) surfaces of 4H-SiC [26].…”
Section: Porous Sic Preparation 15mentioning
confidence: 99%
“…Plenty of experimental efforts have been devoted to explore the oxidation process of these silicon carbide materials, while limitation exists for reaching temperature higher than 2000 K as well as understanding the break and formation of molecular bonding during chemical reaction. [8][9][10][11][12][13][14][15][16][17] Besides, recent studies on compressive properties of SiC composite materials also found temperature-dependent phenomena and attributed them to the oxidation of SiC. Therefore, it is difficult to provide a clear explanation due to the limitation of observation condition.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical reaction in these (11-2-n) and (11-2n) faces showed the polarity like the (0001) Si-and (000-1) C-faces, respectively. Though the specific surfaces such as 4H-SiC {1-102} and 6H-SiC {1-103} were reported as the quasi-polar planes [8,9], all the pyramidal planes around 60 o -and 120 o -inclined faces from the (000-1) C face will show the polarity.…”
Section: Resultsmentioning
confidence: 99%